Objective Outcomes Following Semi-Constrained Total Distal Radioulnar Joint Arthroplasty - Bizimungu, Remy S.; Dodds, Seth D. (Journal of Wrist Surgery, 2013)
A dysfunctional distal radioulnar joint (DRUJ) can significantly compromise an individual's forearm rotation, grip, and weight bearing at the hand and wrist. This retrospective study reports surgeon- and therapist-collected objective wrist function and subjective pain scores of 10 patients who received the Scheker total DRUJ prosthesis. A review of these patients' medical records was performed to collect preoperative measurements of wrist range of motion (ROM), grip strength, and pain scores (0–10 scale). The degree of pronation, supination, flexion, extension, radial deviation, and ulnar deviation were the outcome measures used to evaluate wrist ROM. Postoperative measurements were collected at a follow up of 5 ± 1.1 years in our clinic (minimum follow-up of 2yrs). Mean final wrist flexion and extension were 32.1 ± 22.8° and 44.8 ± 13.9°, respectively. Mean final supination and pronation were 72.5 ± 14.4° and 69.5 ± 14.6°, respectively. Average grip strength was 54.9 ± 23.7 lbs. The mean pain score was 3.6 ± 3.1. Although there were no statistically significant changes in any of these outcome measures, the Scheker prosthesis improved wrist ROM (with the exception of wrist flexion) and decreased pain. Grip strength decreased by less than 1 lb but was still higher than the postoperative grip strength measurements in the literature for this prosthesis. Because of the self-stabilizing nature of this prosthesis and the satisfactory functional outcomes from this study and other studies, the Scheker prosthesis is still a viable option for DRUJ pathology that is refractory to nonimplant arthroplasties. This is a therapeutic level IV study.
Keywords: distal radioulnar joint; arthroplasty; wrist; Scheker prosthesis